DYNAMIC OF MORPHOFUNCTIONAL CHARACTERISTICS OF SCHOOLCHILDREN IN HIGH MOUNTAINS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The work was aimed at studying the functional development of primary, secondary and senior schoolchildren living in the conditions of the high mountain villages of the Tien Shan-Pamirs. Anthropometric methods, sports and medical functional tests were applied. The features of external respiration function, anaerobic reserve, tests for endurance and working capacity, as well as sports results, interconnected with somatometric indicators, were revealed. Speed and strength indicators were determined, such as running speed for 100 m, cross for 1000 m, the length of the jump from a place, the number of push-ups and pull-ups on the crossbar. It is shown that the growth rates of body weight and length in the middle school period in high mountains lag behind those of their peers in low mountains and valleys. However, in high school students they reach the age norm, their reaction to additional physical and hypoxic loads is predominantly normotonic. These features must be taken into account when young men move to the lowlands for military service or study.
Keywords: highlands, boys, age development, functional tests, somatometry.